Impact of fuel staging on stability and pollutant emissions of premixed syngas flames. (1st December 2016) - García-Armingol, Tatiana; Sobrino, Álvaro; Luciano, Ennio; Ballester, Javier
Abstract: Fuel staging is a common alternative for flame stabilization in the vicinity of the lean blowout limit in gas turbine combustors. Whereas this technique has been normally applied to stabilize very lean flames, fuel staging could also have some effect at richer conditions, due to the modification of the spatial distribution of fuel-air ratio, even for a constant global equivalence ratio. This could bring some benefits in syngas flames, where flashback and instabilities may become the main operating issues. However, no previous reference on the effects of fuel staging on those phenomena has been found in published works. The main objective of this work was, therefore, studying the impact and potential benefits of fuel staging with regard to two important syngas combustion issues: widening the stability range of syngas flames and reducing (or, if possible, avoiding) flashback-induced instabilities. At the same time, the effect on pollutant emissions was determined, with a view to minimize their increase or even to attempt to achieve further reduction. In addition, the influence of the injector geometry was also analyzed by comparing the results of different configurations. The results revealed that, if the secondary injector was properly designed, a small quantity of secondary fuel could be enough for avoiding flashback, at the same time that the pressure fluctuations, in case of flashback-induced instabilities, were almost totally removed without significantly increasing pollutant emissions. This finding could be exploited for practical applications, as fuel staging strategies could be useful to alleviate the operational problems due to syngas burning in lean premixed combustors.